Trophic ecology of Caribbean sponges in the mesophotic zone. Issue 4 (11th December 2020) - Macartney, Keir J.; Slattery, Marc; Lesser, Michael P.
Abstract: Sponges are a crucial component of Caribbean coral reef ecosystem structure and function. In the Caribbean, many sponges show a predictable increase in percent cover or abundance as depth increases from shallow (< 30 m) to mesophotic (30–150 m) depths. Given that sponge abundances are predicted to increase in the Caribbean as coral cover declines, understanding ecological factors that control their distribution is critical. Here we assess if sponge cover increases as depth increases into the mesophotic zone for three common Caribbean reef sponges, Xestospongia muta, Agelas tubulata, and Plakortis angulospiculatus, and use stable isotope analyses to determine whether shifts in trophic resource utilization along a shallow to mesophotic gradient occurred. Ecological surveys show that all target sponges significantly increase in percent cover as depth increases. Using bulk stable isotope analysis, we show that as depth increases there are increases in the δ 13 C and δ 15 N values, reflecting that all sponges consumed more heterotrophic picoplankton, with low C:N ratios in the mesophotic zone. However, compound‐specific isotope analysis of amino acids (CSIA‐AA) shows that there are species‐specific increases in δ 13 CAA and δ 15 NAA values. Xestospongia muta and P. angulospiculatus showed a reduced reliance on photoautotrophic resources as depth increased, while A. tubulata appears to rely on heterotrophy at all depths. The δ 13 CAA and δ 15 NAA values of these sponges also reflect species‐specific patterns of host utilization of both POM and dissolved organic matter (DOM), its subsequent re‐synthesis, and translocation, by their microbiomes.